Bibliometric Analysis of Biochar - Loso Judijanto (West Science Agro, 2026)
Biochar has emerged as a promising sustainable material with diverse applications in agriculture, environmental remediation, and carbon management. This study aims to investigate the global research development, intellectual structure, collaboration patterns, and emerging trends in biochar research through a bibliometric analysis approach. Scientific publications related to biochar were collected from a comprehensive academic database and analyzed using bibliometric techniques, including citation analysis, co-authorship analysis, institutional and country collaboration mapping, keyword co-occurrence analysis, thematic evolution analysis, and density visualization using VOSviewer. The findings reveal that biochar research has experienced substantial growth, with China and the United States representing the most influential contributors in terms of scientific productivity and international collaboration. Highly cited literature indicates that early research primarily focused on soil improvement, carbon sequestration, and agricultural sustainability, while recent studies have increasingly emphasized environmental applications, particularly adsorption, wastewater treatment, heavy metal removal, and engineered biochar development. Keyword analysis demonstrates that pyrolysis, adsorption, surface properties, and pollutant remediation have become central research themes, reflecting a transition toward advanced biochar technologies. This study highlights the multidisciplinary nature of biochar research and provides insights into future directions, including the development of modified biochar materials, circular economy applications, and sustainable environmental management strategies.